2008
DOI: 10.1681/asn.2007070747
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Mortality Among Those with CKD

Abstract: Compared with white individuals, black individuals have a significantly higher risk for death in the general population but seem to have a survival advantage in the ESRD population. Data on the relationship of race to survival in early stages of chronic kidney disease (CKD) are inconsistent. This study evaluated racial differences in mortality among the adult participants of the Third National Health and Nutrition Examination Survey, a population-based survey of community-dwelling individuals. CKD was defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
113
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(122 citation statements)
references
References 31 publications
3
113
2
Order By: Relevance
“…However, the composition of the HCRIC cohort is reflective of the heterogeneity of the U.S. Hispanic population in terms of country of origin and education (1,8,41). Moreover, the socioeconomic disadvantages observed in HCRIC are similar to those found in Hispanics with CKD in a recent NHANES III analysis (8). Also, findings from our cohorts may not be generalizable to all types to kidney disease, such as glomerulonephritis.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…However, the composition of the HCRIC cohort is reflective of the heterogeneity of the U.S. Hispanic population in terms of country of origin and education (1,8,41). Moreover, the socioeconomic disadvantages observed in HCRIC are similar to those found in Hispanics with CKD in a recent NHANES III analysis (8). Also, findings from our cohorts may not be generalizable to all types to kidney disease, such as glomerulonephritis.…”
Section: Discussioncontrasting
confidence: 44%
“…However, this methodology is commonly used in clinical research, and the excellent or substantial agreement between self-reported CHD and the medical record has been previously demonstrated in patients with ESRD (42). Third, we estimated GFR using the MDRD formula, which has not been validated in Hispanics; however, this formula has been used in other studies of Hispanics with CKD (8,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower rate of receiving nephrologist care by the younger black patients with CKD, as described in this study, may be responsible, in part, for their poor outcomes reported in the literature (44)(45)(46)(47). Novel strategies aimed at improving pre-ESRD care for younger black patients and implemented both nationally and at the state level could have far-reaching effects.…”
Section: Discussionmentioning
confidence: 66%
“…Thus, geographic distance from health care may be a contributing factor, though the high incident rate of non-diabetic ESRD among West Virginians remains largely unexplained. Studies associating CKD with poverty in the US largely invoke race as a contributing factor with African Americans and other ethnic minorities generally faring worse than whites, particularly when of lower affluence [14][15][16][17][18][19][20][21]. As reflected in our CKD cohort, a high proportion of West Virginia's population is non-Hispanic white (93.5% vs 65.6% for US) with a low prevalence of African Americans (3.6% vs 12.8% for US) [5,6].…”
Section: Discussionmentioning
confidence: 99%